Vaccine Adjuvants Induce Formation of Intraperitoneal Extracellular Traps in Flounder (Paralichthys olivaceus) - Li, Qian; Chi, Heng; Shi, Xueyan; Gan, Qiujie; Dalmo, Roy Ambli; Sun, Yuan-yuan; Tang, Xiaoqian; Xing, Jing; Sheng, Xiuzhen; Zhan, Wenbin (Frontiers in Cellular and Infection Microbiology, 2022)
Adjuvants are used to increase the strength, quality and duration of the immune response of vaccines. Neutrophils are the first immune cells arrived at the injection site, can release DNA fibers together with granular proteins, so called neutrophil extracellular traps to entrap microbes in a sticky matrix of extracellular chromatin and microbicidal agents. Similar extracellular structures were also released by macrophages, mast cells, and eosinophils, and now generalized as “ETs”. Here we demonstrated that Alum adjuvant stimulation led to peritoneal cells swarming and ETs-releasing in vitro. Moreover, compared to antigen stimulation alone, ETs release was significantly increased after stimulation with antigen-mixed adjuvants and in a time- and dose-dependent. In vivo, we were able to monitor and quantify the continuous changes of the ETs release in the same fish by using the small animal in vivo imaging instrument at different times during the early stages after intraperitoneal immunization. The results showed that the fluorescence signal of ETs in the peritoneum increased from 0 to 12 hours after injection, and then gradually decreased. The fluorescence signals were come from extracellular DNA fibers which sensitive to DNaseⅠ and confirmed by microcopy of peritoneal fluid ex vivo. In summary, this study introduced a new method for detecting ETs in peritoneum of fish in vivo and indicated that ET formation involved in the immune response at the early stage after intraperitoneal immunization to vaccines.